2020
DOI: 10.1103/physrevresearch.2.033073
|View full text |Cite
|
Sign up to set email alerts
|

Ground state phase diagram of the doped Hubbard model on the four-leg cylinder

Abstract: We study the ground state properties of the Hubbard model on a four-leg cylinder with doped hole concentration per site δ 12.5% using density-matrix renormalization group. By keeping a large number of states for long system sizes, we find that the nature of the ground state is remarkably sensitive to the presence of next-nearest-neighbor hopping t. Without t the ground state of the system corresponds to the insulating filled stripe phase with long-range charge-density-wave (CDW) order, and short-range incommen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
73
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 119 publications
(108 citation statements)
references
References 47 publications
29
73
2
Order By: Relevance
“…The oscillation amplitude A cdw of nhfalse(xfalse) becomes significantly smaller as t increases. Similar with previous studies of Hubbard model on the square lattice, [ 51,52 ] our results demonstrate the importance of second‐neighbor electron hopping t which provides a promising pathway to potentially realize superconductivity in doping QSL on the Kagome lattice. However, it is also worth mentioning that even the superconducting correlations can be significantly enhanced by t, quasi‐long‐range superconductivity has not yet been realized on the Kagome lattice.…”
Section: Doping Gapped Spin Liquidsupporting
confidence: 89%
See 1 more Smart Citation
“…The oscillation amplitude A cdw of nhfalse(xfalse) becomes significantly smaller as t increases. Similar with previous studies of Hubbard model on the square lattice, [ 51,52 ] our results demonstrate the importance of second‐neighbor electron hopping t which provides a promising pathway to potentially realize superconductivity in doping QSL on the Kagome lattice. However, it is also worth mentioning that even the superconducting correlations can be significantly enhanced by t, quasi‐long‐range superconductivity has not yet been realized on the Kagome lattice.…”
Section: Doping Gapped Spin Liquidsupporting
confidence: 89%
“…It has been shown in previous studies [ 51,52 ] that the second‐neighbor electron hopping t of the Hubbard model on the square lattice is important to enhance superconductivity and suppress CDW order. In this paper, we will show that this is also true for the lightly doped QSL on the Kagome lattice.…”
Section: Doping Gapped Spin Liquidmentioning
confidence: 99%
“…It would be interesting to conduct a similar analysis for a larger system. The state-of-the-art DMRG allows to study quasi-2d stripes as large 4-by-64 atomic sites [38][39][40][41][42] , and we hope to apply the complex network approach to such systems in the future. Still, already at this point it is instructive to compare our results with what has been found by means of other approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Still, already at this point it is instructive to compare our results with what has been found by means of other approaches. In the recent paper 39 , a detailed DMRG analysis of the Hubbard model phase diagram with hole doping ≤ 12.5% has been conducted (which would correspond to sectors (7,7), (7,8), (8,8) in our case), and it was shown that for such hole concentration and negative values of t ′ , the model is in the Luther-Emery liquid phase 51 which is very stable upon varying U and t ′ . This is consistent with our observation that the signs of QCP fade away for all values of the next-nearest hopping and Coulomb repulsion when we approach this level of doping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation